2013
DOI: 10.1186/1479-5876-11-143
|View full text |Cite
|
Sign up to set email alerts
|

A double blind randomized placebo controlled phase I/II study assessing the safety and efficacy of allogeneic bone marrow derived mesenchymal stem cell in critical limb ischemia

Abstract: BackgroundPeripheral vascular disease of the lower extremities comprises a clinical spectrum that extends from no symptoms to presentation with critical limb ischemia (CLI). Bone marrow derived Mesenchymal Stem Cells (BM- MSCs) may ameliorate the consequences of CLI due to their combinatorial potential for inducing angiogenesis and immunomodulatory environment in situ. The primary objective was to determine the safety of BM- MSCs in patients with CLI.MethodsProspective, double blind randomized placebo controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(180 citation statements)
references
References 38 publications
2
176
1
1
Order By: Relevance
“…These analyses revealed similar results in both groups, suggesting that the administered allogeneic cells did not adversely alter the immunological and lymphocytic profile [13]. …”
Section: Resultsmentioning
confidence: 88%
“…These analyses revealed similar results in both groups, suggesting that the administered allogeneic cells did not adversely alter the immunological and lymphocytic profile [13]. …”
Section: Resultsmentioning
confidence: 88%
“…Their plasticity, immunosuppressive potential, immuno-modulatory properties [18,19], and trophic activity [20,21] make MSCs critical players in tissue homeostasis. For these reasons, MSCs are considered a suitable tool for regenerative medicine and have been already introduced in a number of clinical trials for tissue repair [18,[22][23][24][25]. Although they share similar epitope profiles, MSCs derived from different tissues show significant differences in the differentiation, proliferation, and migration potential, which depend on the tissue they originate from as they receive inputs that directly affect their specification [2,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs also showed great results when transplanted with T cells, controlling inflammatory activity in order to create the proper microenvironment for cell transplantation [24] . The immunomodulating effect of MSCs has also been reported in other clinical trials and MSCs have been shown to play an important role as immunomodulators and angiogenic agents in drug resistant patients as well as in patients with cerebral palsy, critical limb ischemia and kidney transplants [25][26][27][28][29][30][31][32] . In another study conducted with 40 patients, bone regeneration was achieved when a great number of CD34 + cells were transplanted to the lesion site, 20 patients achieved mature bone regeneration, even in the group that received a low number of cells 4 patients achieved bone regeneration.…”
Section: Mesenchymal Stem Cells/bone Marrow Stem Cellsmentioning
confidence: 78%